2017
DOI: 10.1074/jbc.m117.808022
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human telomerase reverse transcriptase gene is modulated by quadruplex formation in its first exon due to DNA methylation

Abstract: DNA secondary structures and methylation are two well-known mechanisms that regulate gene expression. The catalytic subunit of telomerase, human telomerase reverse transcriptase (), is overexpressed in ∼90% of human cancers to maintain telomere length for cell immortalization. Binding of CCCTC-binding factor (CTCF) to the first exon of the gene can down-regulate its expression. However, DNA methylation in the first exon can prevent CTCF binding in most cancers, but the molecular mechanism is unknown. The NMR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Opposite observations were made in case of the CpG19 site, where methylation level was decreased in these anatomical sites. Similar results were obtained by Li et al (2017) after examining hTERT promoter methylation status in PBLs of recurrent and non-recurrent thyroid cancer (TC) patients. They observed that recurrence group showed significantly higher DNA methylation level compared to the non-recurrence cohort.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Opposite observations were made in case of the CpG19 site, where methylation level was decreased in these anatomical sites. Similar results were obtained by Li et al (2017) after examining hTERT promoter methylation status in PBLs of recurrent and non-recurrent thyroid cancer (TC) patients. They observed that recurrence group showed significantly higher DNA methylation level compared to the non-recurrence cohort.…”
Section: Discussionsupporting
confidence: 70%
“…They observed that recurrence group showed significantly higher DNA methylation level compared to the non-recurrence cohort. Moreover, in the recurrence group, DNA methylation level was closely associated with tumor stage and lymph node metastasis of TC patients (Li et al 2017). According to de Wilde et al (2010), investigation of hTERT promoter methylation status in cervical cancer, shows hTERT hypermethylation in 100% of analyzed cancer specimens and 38% of the high-grade precursor lesions in contrast to normal tissues, where only 5% of which presented a positive methylation pattern (de Wilde et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, stabilization of G-quadruplexes was noted to mask binding of the well-studied regulatory factors Sp1 and CTCF at the hTERT promoter 18,68,69 . From our results here, it is likely that 42 .…”
Section: Discussionsupporting
confidence: 58%
“…Conversely, DNA methylation can influence G4 topology [85] and may modulate binding by other G4-associated proteins. For instance, CpG methylation at the hTERT gene promoter was suggested to induce G4 formation, resulting in displacement of the CCCTC-binding factor (CTCF) and elevated transcription [86].…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%